PERDAMAIAN DAN REKONSILIASI: SEBUAH EKSPLANASI KEKERASAN BERBASIS AGAMA DAN UPAYA MELAMPAUINYA - Alexander, Michael (GENEVA: JURNAL TEOLOGI DAN MISI, 2019)
Peace is not just a condition of the absence of direct violence. Peace includes conditions for each group of people to obtain equal rights and opportunities. Religions have an ambivalent role. On the one hand intolerance and discrimination based on religion is a fact in a pluralistic society. On the other hand, religions have the power to promote equality, justice, peace and mutual welfare. This paper will describe both sides: First, by arguing that religious violence is not solely rooted in religious practice. There is a reciprocal relationship between religious practices and the social context. The first is insufficient to bring the contradiction into direct violence. Whereas the second is a necessary prerequisite. However, religion is not merely instrumented by interests. Religion has an inherent potential to actualize violence. At the second part of this paper will be present two correlational approaches of religions oriented towards global ethics and liberation praxis. Both of these orientations are proposed as a way out of the impasse of the relations of religions based on epistemological truth or soteriological criteria. Finally, the reconciliation of religions will be achieved when the dialogue of works that struggled for the welfare of humanity and the earth becomes the common goals and responsibility of religions. Key Words: Peace, religions, ambivalence, violence, common walfare, reconciliation